Perlindungan Hukum Bagi Konsumen Dengan Adanya Klausul Eksonerasi Dalam Perjanjian Baku Sewa Guna Usaha (Leasing) - Rahman, Alfikhi Abdul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The problems examined in this paper are: How is the material content of the exoneration clause in the lease standard agreement that causes losses for consumers of PT. Dipo Star Finance branch of Padang and how the judges consider in deciding the principal case of leasing based on Decision Number 4/Pdt.G/2017/PN.Pdg. In this study, the method used is normative juridical which is descriptive where the datas are sourced from primary and secondary data obtained based on the study of documents analyzed qualitatively. From this research, it can be concluded that at the time of making the finance lease agreement there is a will of disability regarding article 29 of the lease agreement and is an exoneration clause that is very detrimental to the consumer. Lesse does not know that collateral for other agreements is a guarantee of the object of the agreement that has paid off. Based on the judgment of the judge and the statement from the witness of the agreement law, article 29 of the lease agreement binds both parties based on the principle of pacta sunt servanda, but no statement or word is found which confirms that the guarantee for the agreement that has ended is a guarantee against other agreements, so that the guarantee becomes multi-interpretation. Article provisions relating to agreement one with other agreements in the agreement is very detrimental to consumers and contrary to article 10 letter (c) of Law Number 8 of 1999 concerning Consumer Protection.